2015
DOI: 10.5014/ajot.2015.015008
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Occupational Therapy Students’ Beliefs About Knowledge and Knowing

Abstract: Research has demonstrated the importance of beliefs about knowledge and knowing, or epistemic and ontological cognition (EOC), to learning and achievement; however, little research has examined occupational therapy students' EOC or determined whether occupational therapy programs promote its development. This study examined changes in EOC over 18 mo of didactic coursework in an occupational therapy program. Thirty-one students completed the Epistemic Beliefs Inventory at the beginning, middle, and end of 18 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…As Greene et al (2008) conjectured, it may be unusual for an individual to have naïve ontological cognition and at the same time hold sophisticated beliefs about the source of knowledge. These results are also consistent with Mitchell's (2015) findings that general ontological cognition was more sophisticated than general epistemic cognition at the beginning, middle, and end of the didactic coursework in an OT program. Although their epistemic cognition became more sophisticated over the course of this study, students continued to hold relatively strong beliefs in an omniscient authority as a source of knowledge at the post-didactic testing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As Greene et al (2008) conjectured, it may be unusual for an individual to have naïve ontological cognition and at the same time hold sophisticated beliefs about the source of knowledge. These results are also consistent with Mitchell's (2015) findings that general ontological cognition was more sophisticated than general epistemic cognition at the beginning, middle, and end of the didactic coursework in an OT program. Although their epistemic cognition became more sophisticated over the course of this study, students continued to hold relatively strong beliefs in an omniscient authority as a source of knowledge at the post-didactic testing.…”
Section: Discussionsupporting
confidence: 90%
“…Individuals first begin believing in the complexity and tentative nature of knowledge before they move away from strong beliefs in an omniscient authority as the source of knowledge. Consistent with this theory, Mitchell's (2015) longitudinal study of EOC in OT students found that ontological cognition was more sophisticated than epistemic cognition at all points in time during the didactic portion of an OT program. Further, over the course of the didactic portion of the OT program, there were changes in epistemic cognition, but no changes in ontological cognition, perhaps because ontological cognition had already matured.…”
Section: Epistemic and Ontological Cognitionmentioning
confidence: 72%
“…There probably is a right answer, but each will have personal opinions/ biases." This finding was consistent with Mitchell's (2015) finding wherein departing students did not deviate significantly in their domain general beliefs about SKCK over time, and were below the median initially and when departing.…”
Section: Simple and Certain Knowledge -Domain Generalsupporting
confidence: 89%
“…The mFQS has been used in previous studies of OT students (Mitchell, 2014(Mitchell, , 2015. Although no reliability or validity data have been published for this instrument, the mFQS provided a holistic measure of OT-specific EOC (discipline specific) and afforded the OT students the opportunity to explain their rationale for their mFQS rating.…”
Section: Tools Used To Evaluate Students' Eoc and Additional Data Colmentioning
confidence: 99%
See 1 more Smart Citation